Hubungan Dukungan Sosial dengan Minat Belajar Pada Anak Jalanan Di Save Street Child - Dwi Prasetyo; Amanda Pasca Rini (Journal of Social, Culture, and Language, 2024)
This research aims to determine whether or not there is a positive and significant relationship between social support and interest in learning among street children at Save Street Child. The method designed for this research includes quantitative research. The population in this study was taken from students from the Save Street Child community. The sampling technique used in this research was the Purposive Sampling technique, the number of samples in the study was 80 children. Data collection in this research used a Linkert model scale, namely a scale of social support and interest in learning. The results of product moment correlation using SPSS version 21.0 of this research show that social support is positively and significantly related to street children's interest in learning at Save Street Child. This is proven by an r value of 0.255, and a significance value of 0.0220.05. The hypothesis states that there is a relationship between social support and interest in learning among street children at Save Street Child. The higher the level of social support, the higher the child's interest in learning. Keywords : Social Support, Interest in Learning, Street Children